The Influence of Leadership Discipline on the Quality-of-Service Implementation of Nonformal Education Program - Abdul Rahmat; Henny Suharyati; Widyatmike Gede Mulawarman; Okke Rosmaladewi; Marsha Angelina US (Universitas Negeri Semarang, 2023)
Study This aim For analyze magnitude influence discipline leadership to quality service implementation of package B non- formal education programs study This writer choose type study quantitative with use method studies descriptive, ie directed method For solve problem with method expose or describe What exists results research. As a main data collection tool used a questionnaire to be tested for validity and reliability. The number of samples in the study were 28 employees. As for the method data analysis using analysis path. From the results study show that discipline leadership form discipline self (X1) and discipline group (X2) separately simultaneous influential to quality service implementation of package B (Y) program of 0.763 or 76.3%. Discipline form discipline self (X1) independently Partial influential to quality services (Y) at the North City Sub District Office of Gorontalo City for 0.260 2 = 0.068 or 6.8%. Contribution aspect discipline This including small Because employee Not yet can arrange self Alone For interest organization, where Still there is more employees attach importance interest personal than task basically in the office. Discipline form discipline group (X2) separately Partial influential to quality service (Y) of 0.650 2 = 0.423 or 42.3%. Contribution aspect discipline This Already well, because employee Already try fulfil standard size achievements that have determined organization, so standard the made reference in work.